Ferric reducing anti-oxidant power assay in plant extract (Bangladesh Journal of Pharmacology, 2016)
The ferric reducing anti-oxidant power (FRAP) assay involved the following steps:  a) preparation of samples, b) reactions and c) finally measuring absorbance of sample and standard at 700 nm using spectrophotometer. The samples were methanolic extract, different fractions (n-hexane, chloroform) and standard ascorbic acid. The solutions prepared were buffer solution (pH 6.6), 1% potassium ferricyanide solution, 10% trichloroacetic acid and 0.1% ferric chloride. Video Clip of Methodology:Ferric reducing anti-oxidant power assay: 21 min 18 sec   Full Screen   Alternate